AB0813 Proposal for the constitution implementation and development of the program of centers of excellence in osteoarthritis in latin america. (15th June 2017) - Santos-Moreno, P; Arape, R; Chacon, R; Franco, L; Riera, H; Caballero, C; Quintero, M
Abstract : Background: Osteoarthritis (OA) is the most prevalent disease in the Americas, with an estimated prevalence of 5–10% of the population. These patients have difficulties accessing the clinic, as well as poorly successful therapeutic programs. We plan to develop a program of Centers of Excellence (CoE) in OA, to meet and respond to these needs, generate data and local research applicable to our health systems. Objectives: In a first phase: To create OA pilot centers in Venezuela and Colombia under the CoE scheme, defined in REAL-PANLAR project (Panamerican league of associations for rheumatology project for implementation of CoE in Rheumatoid Arthritis). In a second phase under the auspices of PANLAR to create the Pan American Network of Centers of Excellence in OA (CEOA). Methods: A systematic review of the literature in global and regional databases (Pubmed, Medline, Scopus, Lilacs) was conducted and through a Delphi-modified methodology and a consensus of experts, naming a coordinator by subject, we established the conceptual bases and defined OA Center of Excellence. Results: The group proposes: 1. Clinical detection and early diagnosis of OA, discarding false positives and diagnosing early OA; 2. Model of patient-centered and multidisciplinary care: frequency of care are to be established according to the conditions of the patient and the multidisciplinary team. 3. Implementation of a specific clinical register of OA with indexes such as WOMAC, Lequesne and also EuroQol and definition of socioeconomic characteristics. 4. Paraclinics and Imaging: Each patient will be given a general laboratory study at admission and then every two years including a metabolic profile. Conventional Rx of hands, hips, knees or lumbosacral column depending on the location and then annual or depending on the evolution. Ultrasound, upon admission to the program, six month later, if synovitis was detected, for redefining the treatment and then annually for evaluation of the articulatory damage; CT and MRI when deemed necessary (OMERACT) 5. Definition of the disease management program in axes: treatment protocol of pain with sequential treatment lines, DMOADs, viscosupplementation, Glucosamine + Chondroitin, Strontium Ranelate, Piascledin; Alternative Medicine and Surgical Treatment 6. Establishment of a management program that includes Structure, Process and Outcome Indicators to define the CEOA as Standard, Optimal and Model. 7. Education modules for patients and families; Continuing Medical Education for all members of the multidisciplinary team; Generation of research in the areas above mentioned. Conclusions: The unmet needs in OA determine the implementation of units of CEOAs, to promote management knowledge, and define T2T strategies, in order to improve clinical outcomes, reducing disability and consequently economic and social costs. References: REAL-PANLAR Project for the Implementation and Accreditation of Centers of Excellence in Rheumatoid Arthritis in Latin America: A Paper From REAL-PANLAR Group on Improvement of Rheumatoid Arthritis Care in Latin America Establishing Centers of Excellence. Santos-Moreno P, Galarza-Maldonado C, Caballero-Uribe CV, et al. J Clin Rheumatol. 2015 Jun;21(4):175–80. Disclosure of Interest: None declared